An interoperability model for supporting reliability and power-efficient routing in MANETs. (19th March 2009) - Safa, Haidar; Artail, Hassan; Shibli, Rami
Handheld devices in Mobile Ad hoc Networks (MANETs) use different communication technologies and are equipped with different software/hardware processing capabilities. This multi-level heterogeneity poses a serious challenge on the performance of such networks. This paper proposes an interoperability model for supporting coexistence between heterogeneous devices and power-efficient routing in a mobile environment. The model is represented through a three-layered paradigm: a communication service layer that deals with available communication capabilities; a communication capability layer that is responsible for controlling and managing the lower communication service layer; and a communication interface layer that provides the applications with a unified public interface. The paper focuses on the architecture and design of the system, and also presents simulation results to show the impact of the proposed model on the network performance.